Influence of plyometric training on the level of speed ability with changes of direction in ice hockey - Knechta, M.; Cillík, I.; Zhánel, J. (Studia Sportiva, 2021)
AIM: Speed skills are among the decisive factors in sports performance in ice hockey. Therefore, it is necessary to examine them in all age categories. Our goal was to determine the effect of plyometric exercises on the level of running and skating speed at 40 m with changes of direction in young hockey players aged 14-15 years.